2014
DOI: 10.1186/1471-2164-15-590
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome sequencing reveals chemotype-specific gene clusters in the toxigenic black mold Stachybotrys

Abstract: BackgroundThe fungal genus Stachybotrys produces several diverse toxins that affect human health. Its strains comprise two mutually-exclusive toxin chemotypes, one producing satratoxins, which are a subclass of trichothecenes, and the other producing the less-toxic atranones. To determine the genetic basis for chemotype-specific differences in toxin production, the genomes of four Stachybotrys strains were sequenced and assembled de novo. Two of these strains produce atranones and two produce satratoxins.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 49 publications
4
68
0
Order By: Relevance
“…Despite the fact that PKS-III is not generally known from the fungi, all of the Ceratocystidaceae genomes that were examined here showed a highly conserved cluster that contained a homolog of the gene encoding chalcone synthase A (CHS). This cluster was also very similar to that reported in Stachybotrys chlorohalonata (Semeiks et al 2014). Few studies have examined the role of this enzyme in fungi, but expression analyses have revealed that all of the PKS-III genes examined so far, are responsible for the biosynthesis of polyketide pyrones and resorcinols (Hashimoto et al 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Despite the fact that PKS-III is not generally known from the fungi, all of the Ceratocystidaceae genomes that were examined here showed a highly conserved cluster that contained a homolog of the gene encoding chalcone synthase A (CHS). This cluster was also very similar to that reported in Stachybotrys chlorohalonata (Semeiks et al 2014). Few studies have examined the role of this enzyme in fungi, but expression analyses have revealed that all of the PKS-III genes examined so far, are responsible for the biosynthesis of polyketide pyrones and resorcinols (Hashimoto et al 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Comparison of the genomes of three S. chartarum strains representing both chemotypes as well as one strain of S. chlorohalonata revealed the presence of common, but also of chemotype-specific, gene clusters. These were attributed to the biosynthesis of satratoxins and atranones, respectively (Semeiks et al 2014). Two isolates of S. chartarum (IBT 7711 and IBT 40293) produced macrocyclic trichothecenes and contained genes that were suggested to be involved in the respective biosynthetic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few biosynthetic gene clusters for trichothecenes have been described from fungi other than Fusarium species, notable examples being from Trichoderma and Stachybotrys species [49, 50]. The A .…”
Section: Resultsmentioning
confidence: 99%